Differences In Social Habits Between British And American People - Salsabila; Asla Alayya; Riska Rahmadhani; Rahmat Fais; Suadi (Yayasan Al-Afif, 2026)
This research examines the differences in social habits between British and American societies in four main aspects: communication style, attitude toward time, politeness, and patterns of social interaction, with implications for English language learning in Indonesia. Using a descriptive qualitative approach with a multi-method design, primary data were collected thru in-depth interviews with 15 key informants (British-American expatriates in Indonesia) and observations of 12 authentic video vlogs, supplemented by a review of 30 peer-reviewed journals (2015–2026). The results show that the British apply indirect-formal communication (understatements, sarcasm), moderate punctuality with a sacred queuing culture, traditional restraint in politeness, and slow interaction via small talk about the weather; conversely, Americans are direct-explicit (open praise), absolute time-is-money, friendly-informal politeness (small talk, touch), and quick networking. The findings align with Edward T. Hall's theory of high-context (British) vs low-context culture (American) and Hofstede's dimensions. The contribution of the research is the development of cultural code-switching for Indonesian EFL learners to reduce cross-cultural misunderstandings, with recommendations for role-play scenarios and AI digital modules. Future research is suggested to include field ethnography in the UK-US.